Towards an Objectivistic Axiological Theory: Husserl's Phenomenological Challenge to Naturalism in Ideas I - Pesik, Tobian Habel (MELINTAS, 2025)
The question of naturalism, as a philosophical theory of reality, has been a perennial problem in philosophy. In the contemporary era, naturalism is backed by the scientific enterprise, giving birth to the worldview of scientific naturalism. In this essay, I explore the problems posed by such a scientific version of naturalism. Edmund Husserl, in his work Ideas I, gives several arguments against scientific naturalism, which can be exploited on their own without reference to the larger context of the work's contributions to the development of transcendental phenomenology. Besides arguing that naturalism is inherently self-defeating, Husserl argues that naturalism as a theory of reality cannot accommodate a viable account of human experience, particularly of our perception of ideas and essences, objects that are labelled as ideological extravagance by naturalism. Furthermore, because Husserl's arguments against naturalism can be exploited on their own, they can be employed in other fields of philosophy in which naturalism poses a problem, such as metaethics.